Protection of the Weaker Party to a Property Development Contract under Polish Law. Implementation of the Model of the State’s Protective Duties in Practice - Florczak-Wątor, Monika (Teisė, 2019)
[full article and abstract in English] This study examines the mechanism of the protection of customers of property developers that was introduced into Polish legal system by the Property Development Act adopted on 16 September 2011. Those customers are the weaker party to a property development contract that should be protected by the State. The article presents the very concept of the Polish property development contract, its substance and legal forms as well as its practical aspects. This issue of the protection of customers of property developers is of a great importance not only in Poland but also in other European countries that have experienced a boom in the real estate market in the last decade. The article discusses also the issue of the compatibility of the Property Development Act with the model of the State’s protective obligations in horizontal relations that has been established under the Constitution of the Republic of Poland of 2 April 1997. The paper concludes by presenting some postulates of amendments to the Property Development Act submitted by consumer organizations, industry representatives and entrepreneurs as well as a very comprehensive draft of the amendment presented in May 2018 by the President of the Office of Competition and Consumer Protection. This draft is currently at the stage of inter-ministerial consultations and it is difficult to foresee whether the new solutions will be adopted by Parliament in such a form.